Pattern of tobacco use among adolescents in urban slums of Jorhat, Assam - Das, Netri; Tasa, Anadi S.; Medhi, Anuradha H. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco use is a leading cause of preventable death worldwide and an estimated 250 million children and adolescents in developing countries die prematurely because of tobacco consumption. The objectives of the study were to determine the pattern of tobacco use among the adolescents and assess the factors associated with its use in urban slums of Jorhat, Assam. Methods: A community-based cross-sectional study was conducted in two randomly selected urban slums of Jorhat district from September 2015 to February 2016 among 110 adolescents using predesigned pretested proforma. Data were analyzed using SPSS - trial version 16; risk analysis was done using odds ratios with 95% confidence intervals. Results: 106 (96.36%) adolescents had ever used a tobacco product and 97 (88.18%) were current users. 57.73% consumed smokeless form and 3.1% used smoking form exclusively while 39.17% used both smoking and smokeless tobacco. Exclusive smokeless tobacco use was more common among girls. Smoking as well as combined smoking and smokeless tobacco was more common among boys. Gutkha was most common smokeless product (94.84%) and cigarette was commonest smoking form (34.02%) used. Awareness regarding its harmful effects was high (77.28%). Tobacco use in family is significantly associated with current use of tobacco (OR 5.88). Conclusions: Tobacco consumption is an emerging threat to health of adolescents in urban slums. Smokeless tobacco use is high in our study, especially among girls. Tobacco use by family is a major reason behind using tobacco indicating an urgent need to carry out behaviour change communication (BCC) activities among adolescents and their family members.